PEMETAAN KERUSAKAN HUTAN MANGROVE DI KECAMATAN MANDAH KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Syafruddin, Yudha Saktian (STKIP PGRI Sumbar, 2014)
This study aims to analyze (1) Species of mangrove forest vegetation, (2) The closure of mangrove forest vegetation, (3) The density of mangrove forest vegetation, (4) Distribution of mangrove forest vegetation, (5) The damage of mangrove forests, (6) The Mapping of mangrove forest damage in Mandah District of Indragiri Hilir in Riau Province. This study used a descriptive quantitative research. The data sources are primary data and secondary data. The sample taken by using Line Transect Plot, with 5 transect lines, each transect has 3 sample plots with a total sample are 15 plots. The data analysis technique that used is the equation for calculating the percentage of the closure of mangrove forest vegetation, the density of mangrove forest vegetation, distribution of mangrove forest vegetation, and the damage of mangrove forest, The Mapping of mangrove forest damage using Arc View 3.3. software based on the result of calculation. The result on the analysis data obtained that 1). Species of mangrove forest vegetation : Bakau / Rhizophora Mucronata, Nyirih / Xylocarpus Granatum, Pidada / Sonneratia Alba, Nipah / Nypa Fruticans, Behe / Aigiceras Floridum, Tuntum / Aigiceras Corniculatum. 2). Percentage of Bakau vegetation closure was 15.1002%, Nyirih 5.28%, Pidada 4.9812%, Nipah 57.4701%, Behe 17.1665%, and Tuntum 0.0004%. 3). The density of mangrove forest vegetation with 1500 m2 area that is Bakau vegetation which accounted as many as 161 trees, 62 Nyirih trees, 65 Pidada trees, 112 Nipah trees, 95 Behe trees, and 5 Tuntum trees. 4). The pattern of distribution of mangrove forest vegetation at the research location classified to the pattern of stucked distribution. 5). The damage of mangrove forest at the research location classified as moderate damage and 6). The Mapping of mangrove forest damage is show in the form of spatial with the difference of color gradation on the of mangrove forest damage. In addition, it can be concluded that the damage of mangrove forest in the Mandah District of Indragiri Hilir in Riau Province categorized in moderate damage.